Discovery of nanophase iron particles and high pressure clinoenstatite in a heavily shocked ordinary chondrite: Implications for the decomposition of pyroxene. (1st March 2020) - Guo, Zhuang; Li, Yang; Liu, Shen; Xu, Huifang; Xie, Zhidong; Li, Shijie; Li, Xiongyao; Lin, Yangting; Coulson, Ian M.; Zhang, Mingming
Abstract: Although pure metallic iron (i.e. that with an Fe content of greater than 99%) commonly occurs in achondrites, and within the returned soil from asteroids or the Lunar surface, it is rarely found in ordinary chondrites meteorites. Abundant nanophase iron particles (np-Fe 0 ) were identified in pyroxene glass, within the shock melt vein of Grove Mountains (GRV) 022115, which is an ordinary (L6) chondrite, with a shock stage determined as S5. The association of np-Fe 0, highly defective high pressure clinoenstatite (HP-CEn), silica glass, as well as vesicles, embedded in a pyroxene glass selvage within the shock melt vein in this meteorite suggests that these phases formed as the result of decomposition of the host pyroxene grain, a process induced by the shock event that affected GRV 022115. The reaction to account for this mineral breakdown can be written as: FeSiO3 → Fe + SiO2 + 1/2O2 ↑ (MgSiO3 remain in the HP-CEn). The pressure and temperature condition attending this reaction are estimated at 20–23 GPa and over 1800 °C, as indicated by the surrounded high-pressure mineral assemblage: ringwoodite, majorite, and magnesiowüstite. This study provides evidence to the formation of np-Fe 0 derived from pyroxene, and HP-CEn quenched metastably in such shocked vein could preserve the metastable phase transitions history record.